2017
DOI: 10.14254/2071-789x.2017/10-2/15
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Trust in Physiciants as an Antecedent of Satisfaction with Medical Servcies

Abstract: ABSTRACT. Trust in the patient-physician relationship represents the power to shape behaviors of both sides. It may have also the value of being the precondition of patient satisfaction with medical services. Therefore, the purpose of this paper is to investigate the role of trust as an antecedent of patient satisfaction, based on the nationwide, representative sample. The multiple regression analysis has been applied. The study shows that all three identified dimensions of trust are important and statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…From the above, it can be said that accepting the right hypothesis imposed (there is a correlation between trust and patient satisfaction), is consistent with the findings of the study [56] and study [61]. The results of Table 10, shown in Figure 4, show an incorporeal impact of trust factors on patient satisfaction, and this finding is consistent with studies [62] and study [63] and study [64] as indicated by the calculated value (F) of (126.727) which is greater than the scheduling value (1.64), to show the explanation of the confidence factors related to (communication, Competence, and quality of service, which lead to patient satisfaction with the service provided by the researched medical clinics and reality (0.519), the remaining value is not included in the current study model. Sub hypotheses can be interpreted as follows:…”
Section: Figure 2 Structural Model Of Trust Variablesupporting
confidence: 89%
“…From the above, it can be said that accepting the right hypothesis imposed (there is a correlation between trust and patient satisfaction), is consistent with the findings of the study [56] and study [61]. The results of Table 10, shown in Figure 4, show an incorporeal impact of trust factors on patient satisfaction, and this finding is consistent with studies [62] and study [63] and study [64] as indicated by the calculated value (F) of (126.727) which is greater than the scheduling value (1.64), to show the explanation of the confidence factors related to (communication, Competence, and quality of service, which lead to patient satisfaction with the service provided by the researched medical clinics and reality (0.519), the remaining value is not included in the current study model. Sub hypotheses can be interpreted as follows:…”
Section: Figure 2 Structural Model Of Trust Variablesupporting
confidence: 89%
“…Differences in the availability of healthcare resources, patient and provider cooperation, affect the quality of healthcare services and patient outcomes differently. Efficient management of resources and processes influence the quality of health services (Mosadeghrad, 2014;Persona et al 2008;Battini & Rafele 2008;Krot & Rudawska, 2017;Miguel Cruz & Guarín 2017;Gianino et al 2017). Many studies of amenable and preventable mortality and their determinants are based on the production function of health (Nolte & McKee, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…kebahagiaan pelanggan dapat diperoleh dari kepercayaan dan dedikasi konsumen kepada penyedia jasa [21]. Kepercayaan pasien terhadap kompetensi tenaga medis dapat mempengaruhi kepuasan terhadap pelayanan yang diberikan [15]. Kepercayaan pelanggan dalam konteks aplikasi seluler mempengaruhi kepuasan pelanggan [2] karena kepercayaan dalam lingkungan virtual lebih signifikan karena kepercayaan dalam lingkungan virtual didasarkan pada janji daripada kontak langsung.…”
Section: Pengembangan Hipotesisunclassified